TikTok live Streaming: The Role of Influencers in Shaping Consumer Purchase Decision - Nadia, Nadia; Indri, Marta (PT Inovasi Pratama Internasional, 2024)
This study aims to determine the role of influencers in TikTok live streaming, promotion and trust in purchase urchase intention. The research method used in this research is descriptive quantitative. The sample in this study were 100 people. The sampling technique used is nonprobability sampling with saturated sampling. The approach used in this study was accidental sampling. The types of data used in this study are primary data and secondary data, where secondary data is used to strengthen the background of the problem. The measurement scale used is a questionnaire with a Likert scale of 1-5. The tests carried out in this study are validity and reliability tests, hypothesis testing, inner model, outer model and r square. The tool used to test the hypothesis is the Structural Equation Model (SEM) with the SPSS. The results of this study are that promotion and trust have a positive and significant effect on TikTok Live influencers in Yogyakarta, while promotion and trust have a positive effect on TikTok consumer buying interest, while the Influencer variable mediates the relationship between promotion and consumer buying interest TikTok Live in Yogyakarta.